A world-involving theory of agency: review of Sensorimotor Life: An Enactive Proposal by Ezequiel Di Paolo, Thomas Buhrmann, and Xabier Barandiaran. Oxford University Press, Oxford, 2017. (April 2022) - Ramírez-Vizcaya, Susana
Sensorimotor theory of perception has been criticized for its ambiguity about the need for internal representations and the lack of a proper account of agency and subjective experience. The book under review offers a compelling non-representational, world-involving interpretation, and operationalization of this theory, showing that alternatives to representationalism are viable. It also provides a thought-provoking theory of sensorimotor agency and the pre-reflective experience of action that builds on the enactive notions of autonomy and sense-making. The account provided in this book fits into a radically embodied, enactive, and extended cognitive science. However, the notion of the environment requires further conceptual clarification by the enactive camp.